EVALUATION OF POTENTIAL APHRODISIAC ACTIVITY OF HIBISCUS CANNABINUS (LINN) SEEDS IN MALE ALBINO RAT - VARSHA ZADE; DINESH DABHADKAR (International Journal of Pharma and Bio Sciences, 2013)
The Hibiscus cannabinus (H. cannabinus) seed is used for curing male infertility and impotency in traditional medicine. However, the validity has not been scientifically evaluated. Therefore, the present study was undertaken to evaluate the effect of H. cannabinus seed on the sexual behaviour of male rats. Sixty six rats were randomized into five groups and were treated as one control group, three experimental and one standard group. All the extract doses resulted in significant increase in mount frequency, intromission frequency and reduction in mount and intromission latency in experimental animals. The animal group treated with H. cannabinus seed at dose of 400 mg/kg shows a maximum increase in the orientation activity toward female rats. This group also showed significant increase in serum testosterone concentrations. Results of this study led to a conclusion that the aqueous seed extract of H. cannabinus increased the blood testosterone concentrations and this may be the mechanism responsible for its aphrodisiac effects and various masculine behaviour. It may be used to modify impaired sexual functions in animals. Phytochemical screening revealed the presence of alkaloids, flavonoids, steroids, tannins and saponines.